The doublecross : (and other skills I learned as a superspy) - Pearce, Jackson (Bloomsbury, 2015)
Overweight and non-athletic, twelve-year-old Hale may have been born and raised to be a spy for the Sub Rosa Society but it seems he is unlikely to become a Field Agent until his parents are captured by the evil League and Hale sets out on a solo mission to save them.